An egg‐laying device to estimate the induction of sterility in Ceratitis capitata (Diptera: Tephritidae) sterile insect technique programmes. (24th September 2018) - Suárez, Lorena; Buonocore Biancheri, María Josefina; Murúa, Fernando; Rull, Juan; Ovruski, Sergio; de los Ríos, Claudia; Escobar, Jorge; Schliserman, Pablo
Abstract: Area‐wide environmentally friendly pest control methods such as the sterile insect technique (SIT) are being developed and improved to contribute in managing agricultural, environmental and public health problems. A key aspect to evaluate performance of sterile males is to directly measure sterility induction in the field. Sterility induction has been estimated for tephritid fruit flies by recovering egg from host fruit in the field, the method is, however, impractical, and past efforts to develop artificial egg‐laying devices have not prospered. Here, we evaluated response of wild gravid Ceratitis capitata (Medfly) females to long‐distance fruit‐based chemical attractants, visual and tactile stimuli to develop an artificial egg‐laying device. The device combining the most attractive features was further tested under two deployment schemes. Finally, devices and deployment tactics were used to compare fertility levels between feral Medfly females under conventional management and under SIT. Agar spheres wrapped in plastic film, baited with pressed peach juice and visually enhanced with yellow discs received more egg than other combinations of attractive features. Such devices also received more eggs when deployed on fruitless trees and when placed on the orchard perimeter. The egg hatch in an orchard under conventional management was estimated at 86%, whilst egg hatch in an area under SIT was reduced to 31%. The egg‐laying devices are therefore useful to measure sterility induction and can be further improved by refining long‐distance attraction and deployment schemes.